Assessing the Influence of Taxation Knowledge, E-Filing Implementation, and Income Level on Individual Taxpayer Compliance - Briliyanti, Ni Putu Devina; Hasibuan, Henny Triyana (E-Jurnal Akuntansi; Vol 34 No 6 (2024), 2024)
This study investigates the influence of taxation knowledge, e-filing implementation, and income level on individual taxpayer compliance at KPP Pratama West Denpasar. Utilizing the Slovin formula, the sample size was determined to be 100 from a total of 50,616 individual taxpayers representing the research population. Data collection was carried out through a structured questionnaire, and the analysis employed multiple linear regression techniques. The findings reveal that taxation knowledge, the implementation of e-filing, and income level significantly impact taxpayer compliance. These results are underpinned by the Theory of Planned Behavior, which suggests that behavioral intentions influence compliance behaviors, and Attribution Theory, which helps explain how taxpayers perceive the causes of their compliance decisions. Keywords: Taxation Knowledge; E-Filing Implementation; Income Level; Taxpayer Compliance